Identification of river basins within northwestern slope of Crimean Mountains using various digital elevation models (ASTER GDEM, ALOS World 3D, Copernicus DEM, and SRTM DEM) - Tabunshchik, Vladimir; Gorbunov, Roman; Gorbunova, Tatiana; Pham, Cam Nhung; Klyuchkina, Aleksandra (Frontiers in Earth Science, 2023)
Since the end of the 20th century, the use of geographic information systems and digital elevation models has reduced the time required for and improved the quality of morphometric analysis of the relief within river basins. However, researchers are constantly faced with the problem of choosing the most accurate and suitable digital terrain model for their task. Many global, regional, and local digital elevation models are available. In this study, we comparatively analyzed the accuracy of the ASTER GDEM, ALOS World 3D, Copernicus DEM, and SRTM DEM spatial datasets for the purpose of catchment basin modeling for the river basins of the northwestern slope of the Crimean Mountains (Zapadnyy Bulganak, Alma, Kacha, Belbek, and Chernaya Rivers) as an example. For each river basin, we calculated the systematic, root mean square, mean absolute, standard root mean square (Bessel's correction), and centered mean absolute errors by comparing ASTER GDEM, ALOS World 3D, Copernicus DEM, and SRTM DEM data with a 1:100000 topographic map within the considered river basins. We found the smallest error values for the Copernicus DEM and ALOS World 3D datasets; furthermore, we used the Copernicus DEM dataset to model the river basins and sub-basins of the northwestern slope of the Crimean Mountains. As a result, we identified these river basins and sub-basins for the Zapadnyy Bulganak, Alma, Kacha, Belbek, and Chernaya Rivers, which are represented by stream basins, valleys, gullies, and ravine systems.